Laparoscopic liver resection: the current status and the future - Cai, Xiujun (HepatoBiliary Surgery and Nutrition; Vol 7, No 2 (April 17, 2018): Hepatobiliary Surgery and Nutrition, 2018)
Dramatic progresses had been made in the operation in the past 26 years. Procedure was extended to major liver resection, isolated resection of caudate lobe, living donor liver resection and associating liver partition with portal vein ligation for staged hepatectomy (ALPPS). Laparoscopic liver resection became a new group of HPB surgery and the international laparoscopic liver society was established in Paris followed by the first international congress of the society held in Paris in July 2017. This biannual congress would be top convention for surgeons specialized in laparoscopic liver surgery. The advantage of laparoscopic liver resection had been recognized by patients and surgeons and is gradually replacing conventional open liver resection in some experienced institutes worldwide. Most procedures, such as laparoscopic local resection and left lateral segmentectomy, could be routinely performed, but some procedures including laparoscopic hemihepatectomy still need to be further evaluated. For now, the establishment of a training system for laparoscopic liver surgeons became the most important issue for the popularization of laparoscopic liver resection.